Reduction Glossoplasty in a Calf with Bifid Tongue - Lopes, Samara de Paula; Helavel, Michel Abdalla; de Cunha, Isabelle Magalhães; Delecrodi, Raphael; Pereira, Leonardo; Cerqueira, Syntia Dias; Cid, Gabriela de Carvalho; Nogueira Carvalho, Vivian de Assunção; Caldas, Saulo Andrade (Acta Scientiae Veterinariae, 2019)
Background: Fetal malformations are characterized by anatomical changes that compromise an organ or system. Tongue formation in bovines occurs with the fusion of three structures at the end of the fourth week of gestation, and any failure during this stage of embryonic development may lead to tongue malformation. Bifid tongue, also called glossoschisis, is a rare congenital abnormality in any species and is characterized by incomplete fusion of the lateral tongue buds, resulting in a deep groove in the midline of the tongue. The objective of this study was to describe a case of bifid tongue and the procedure of reduction glossoplasty in a calf of the Girolando breed in Tocantins State. Case: A male mixed-breed (Holstein-Friesian × Gir) calf, born from natural mating in the municipality of Araguaína, Tocantins, was clinically assessed in the Sector of Ruminant Clinical Medicine of the Federal University of Tocantins at 2 months of age. The owner reported that the animal exhibited difficulty in suckling after birth and that on inspection of the oral cavity, he observed changes in the tongue and mandible. Clinical examination of the oral cavity revealed the presence of a bifid tongue and abnormal fusion of the mandible in the region of the lower incisive teeth. It was decided to perform a surgical procedure with the aim of improving the animal’s quality of life because the owner wanted to keep it in the farm. An incision was made, followed by removal of the medial rims of the two tines of the tongue, and synthesis was performed, joining the ventral rims of the tongue, beginning at the root and ending at the apex. Discussion: The observed lesions are compatible with bifid tongue and mandibular fissure, both previously reported in other species. The literature has no reports of bifid tongue in bovines. The etiology of fetal malformations is still unclear, and the primary causes known in Brazil include ingestion of toxic plants by the mother, such as Mimosa tenuiflora and Poincianella pyramidalis; infections, with the main viral agents being bovine viral diarrhea virus and blue tongue virus; and teratogenic agents, namely certain medications administered during embryogenesis, e.g., ivermectin. Other potentially teratogenic agents that have not been identified as causes of malformation include radiation, cortisone, benzimidazoles, sulfonamides, folate antagonists, and organophosphates. The intense genetic improvement that the Holstein-Friesian breed has been subjected to, including inbreeding that results in consanguinity, may be a determining factor for the breed carrying mutant alleles. Because the calf in this report was crossbred from parents with Holstein-Friesian ancestry, it could carry mutant alleles that led to the malformation. Another etiology proposed in a study on embryological bases by Goodacre and Wallace (1990) is the persistence of buccopharyngeal membrane and amniotic constriction bands in the region of the branchial arches; this cause cannot be ruled out in the present case. Calves born with fetal malformations generate losses for cattle breeders because the calf dies either before or after birth, which may culminate with the death of the mother or, in cases in which the anomaly is compatible with life, damage to the animal’s development and well-being, as in the present report. Bifid tongue is a rare malformation in bovines, and reduction glossoplasty is essential for the description and improvement of techniques that aid bovine medicine; however, animals subjected to this procedure should not be used for reproduction.